Alzheimer’s Disease: From Genetic Variants to the Distinct Pathological Mechanisms - Sun, Qiying; Xie, Nina; Tang, Beisha; Li, Rena; Shen, Yong (Frontiers in Molecular Neuroscience, 2017)
Being the most common cause of dementia, AD is a polygenic and neurodegenerative disease. Complex and multiple factors have been shown to be involved in its pathogenesis, of which the genetics play an indispensable role. It is widely accepted that discovery of potential genes related to the pathogenesis of AD would be of great help for the understanding of neurodegeneration and thus further promote molecular diagnosis in clinic settings. Generally, AD could be clarified into two types according to the onset age, the early-onset AD (EOAD) and the late-onset AD (LOAD). Progresses made by genetic studies on both EOAD and LOAD are believed to be essential not only for the revolution of conventional ideas but also for the revelation of new pathological mechanisms underlying AD pathogenesis. Currently, albeit the genetics of LOAD is much less well-understood compared to EOAD due to its complicated and multifactorial essence, Genome-wide association studies (GWASs) and next generation sequencing (NGS) approaches have identified dozens of novel genes that may provide insight mechanism of LOAD. In this review, we analyze functions of the genes and summarize the distinct pathological mechanisms of how these genes would be involved in the pathogenesis of AD.